Analyzing Students’ Thinking Processes in Solving Exponential Problems Based on APOS Theory: A Qualitative Study at SMA Negeri 7 Tanjung Jabung Timur - Liawati; Nizlel Huda; Jefri Marzal (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study aims to describe students’ thinking processes in solving exponential problems based on the APOS theory (action, process, object, and schema). This research employed a descriptive qualitative approach conducted in class X Phase E3 at SMA Negeri 7 Tanjung Jabung Timur. The subjects consisted of three students selected through purposive sampling, representing high, moderate, and low ability levels. Data were collected using written tests in the form of open-ended questions and semi-structured interviews to explore students’ thinking processes in depth. The results indicate that students with high ability were able to achieve all stages of APOS, demonstrating a comprehensive understanding and integration of concepts. Students with moderate ability reached the action and process stages adequately but showed limited understanding at the object and schema stages. Meanwhile, students with low ability were only able to perform at the action and partial process stages, relying on procedural steps without deep conceptual understanding. These findings highlight differences in students’ conceptual construction across ability levels.